Short-term mechanical ventilation of air-conditioned residential buildings: A general design framework and guidelines. (1st November 2016) - Ai, Z.T.; Mak, C.M.
Abstract: Ventilation is needed in air-conditioned residential buildings, particularly the bedrooms in nighttime sleeping periods, to maintain an acceptable indoor air quality. Our previous on-site measurements evaluating various ventilation strategies suggest that short-term mechanical ventilation is overall the most appropriate ventilation strategy for air-conditioned residential buildings. However, there is still no a general design framework of short-term mechanical ventilation strategy, which can determine appropriate design parameters, including ventilation period, ventilation frequency, and start concentration of ventilation, based on various combinations of indoor CO2 generation rate, net room volume, infiltration rate, and mechanical ventilation rate. This study for the first time develops such a design framework and then provides the detailed design guidelines. A whole sleeping period of 8 h is divided into many repeated single V -shape ventilation periods; each single ventilation period is comprised of a short-term mechanical ventilation period and a follow-up CO2 build-up period. The single V -shape ventilation process is particularly investigated based on a criterion that the average indoor CO2 concentration is less than but close to 1000 ppm. A high efficient ventilation strategy, namely requiring a minimum total mechanical ventilation period, is a short single ventilation period and a high ventilation frequency. The outcomes of this study are presented in the form of figures and tables, with most parameters normalized, which are useful to assist a rapid ventilation design. Graphical abstract: Highlights: A ventilation design framework developed for air-conditioned residential buildings. Important aspects of the design framework investigated. Step by step ventilation design guidelines provided. Several to dozens of single V -shape ventilation periods needed for an 8-h period.